2017
DOI: 10.1371/journal.pone.0172770
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 90 day repeated dose oral toxicity and reproductive/developmental toxicity of 3'-hydroxypterostilbene in experimental animals

Abstract: 3'-Hydroxypterostilbene (3'-HPT) is one of the active constituents of Sphaerophysa salsula and Pterocarpus marsupium. Despite many proposed therapeutic applications, the safety profile of 3'-HPT has not been established. The present work investigated 90 day repeated oral dose and reproductive (developmental) toxicity of 3'-HPT as a test substance in rats as per OECD guidelines. 90 day toxicity was conducted in sixty Sprague Dawley rats of each sex (120 rats), grouped into six dosage groups of 0 (control), 0 (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…In fact, a 90 day toxicity study showed that rats who were given 3′-HPSB at 20, 80, and 200 mg/body weight/day orally displayed no significant differences in body weight, food intake, absolute organ weight, and hematology. There were also no adverse effects found on biochemical values and any abnormal clinical signs or behavioral changes in rats from a high dose of 3′-HPSB treatment . In our study, mice fed a diet containing 50 and 250 mg/kg 3′-HPSB (equivalent to 0.3 mg and 1.5 mg/mouse/day) showed no overt toxic changes, indicating the safety and chemopreventive efficacy of dietary hydroxylated 3′-HPSB.…”
Section: Discussionsupporting
confidence: 54%
“…In fact, a 90 day toxicity study showed that rats who were given 3′-HPSB at 20, 80, and 200 mg/body weight/day orally displayed no significant differences in body weight, food intake, absolute organ weight, and hematology. There were also no adverse effects found on biochemical values and any abnormal clinical signs or behavioral changes in rats from a high dose of 3′-HPSB treatment . In our study, mice fed a diet containing 50 and 250 mg/kg 3′-HPSB (equivalent to 0.3 mg and 1.5 mg/mouse/day) showed no overt toxic changes, indicating the safety and chemopreventive efficacy of dietary hydroxylated 3′-HPSB.…”
Section: Discussionsupporting
confidence: 54%
“…Histopathology, hematology, clinical chemistry, and urinary balance studies found no alterations induced by PT as compared to controls [ 20 ], thus concluding that orally administered PT, even at the highest dose administered, was nontoxic. More recent studies suggest a no-observed-adverse-effect-level (NOAEL) of 200 mg of 3’-hydroxy-pterostilbene (a natural PT analog)/kg body weight/day in rats after oral administration [ 21 ].…”
Section: Toxicitymentioning
confidence: 99%
“…3′-Hydroxypterostilbene (trans-3,5-dimethoxy-3′,4′-dihydroxystilbene, HPSB), one of the metabolites of pterostilbene, 17 is present in the plants Sphaerophysa salsula and Pterocarpus marsupium and in honey bee propolis. 18 A recent study indicated that HPSB possesses antiadipogenic, anti-inflammatory, antioxidant, anticolitis-associated colonic tumorigenesis, and SIRT-1 inhibitory activities, 19,20 but its role in obesitypromoted colitis remains unknown. This study aimed at investigating the protective effect and related molecular mechanisms of HPSB on the high-fat diet (HFD)-promoted DSS-induced colitis animal model.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Stilbenoids, including resveratrol, oxyresveratrol, pterostilbene, and piceatannol, are widespread in various fruits, vegetables, and edible plants. 3′-Hydroxypterostilbene ( trans -3,5-dimethoxy-3′,4′-dihydroxystilbene, HPSB), one of the metabolites of pterostilbene, is present in the plants Sphaerophysa salsula and Pterocarpus marsupium and in honey bee propolis . A recent study indicated that HPSB possesses antiadipogenic, anti-inflammatory, antioxidant, anticolitis-associated colonic tumorigenesis, and SIRT-1 inhibitory activities, , but its role in obesity-promoted colitis remains unknown.…”
Section: Introductionmentioning
confidence: 99%